Expedições investigativas em espaços não formais no ensino de ciências e suas potencialidades no ensino fundamental - Müller, Diana Denise Radiske (2022)
Science education aims to make the student come to share meanings in the context of science. The objective of the research is to verify the contributions and potentialities of the use of non formal spaces for science teaching, in thefinal years (6th grade to 9th grade) of Elementary School, from a systematic bibliographic review, and the contextualization of Investigative Expeditions carried out with elementary school students in two municipal schools in Agudo/RS. Therefore, the stud y considered the use of nonformal spaces in science teaching, describing paths and possibilities for the teaching and learning process. The methodology consisted predominantly of qualitative research, of the case study type, in addition to a set of method ological techniques that support and describe some experiences lived by the researcher in nonformal spaces in the city of Agudo/RS. The research data analysis techniques involved Content Analysis and Scientometric Analysis. The research is organized into five chapters, and its actions considered the literature review and the production of four manuscripts on the use of nonformal spaces. Thus, the results describe some experiences and possibilities about the use of non formal spaces in science teaching and Therefore, the results show that the use of nonpaths taken in the municipality of Agudo/RS. formal spaces can contribute to student learning, make classes more interesting, optimize knowledge and give meaning to subjects previously developed at school, e specially in relation to the reality in which the school is inserted and possibilities for the use of notsorecognized spaces; in addition to contributing with reflections that can qualify the actions in science teaching of teachers and researchers in the way, the research contextualized the educational importance of nonarea. In this formal spaces and their potential in science teaching, as an innovative and diversified strategy, content complementation and motivation for the teaching and learning process .